The Diagram of Moral Vices in Eudemian Ethics II 3 - Echeñique, Javier (Revista Archai, 2017)
This article provides an interpretation of the eloquent diagram of moral dispositions to be found at Eudemian Ethics II 3. In the first section the double thesis is defended according to which the third column of this diagram, integrated by a list of moral virtues, is an interpolation, and that the original two-column diagram, listing the moral vices, contributes in an original way to elucidating the intermediate nature of moral virtue. In the second section I examine the differences between the EE II 3 diagram and the diagram referred to in Nicomachean Ethics II 7, partly as an attempt to reinforce the thesis defended in the first section.